2018
DOI: 10.1002/mc.22831
|View full text |Cite
|
Sign up to set email alerts
|

PIEZO1 functions as a potential oncogene by promoting cell proliferation and migration in gastric carcinogenesis

Abstract: Gastric cancer (GC) is one of the most common malignancies in Asian areas. PIEZO1 has been implied to regulate epithelial homeostasis to play an important role in physiological processes. It is also related to tumor initiation and progression. However, the role of PIEZO1 has not yet been explored in GC. The expression of PIEZO1 in GC cell lines and primary samples was determined by qRT-PCR and Western blot. The clinical correlation of PIEZO1 in GC was evaluated by immunohistochemistry on tissue microarray. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 39 publications
2
80
0
Order By: Relevance
“…Recent studies have reported a role for the Piezo1 channel in regulating cell migration in endothelial cell and cancer cells . In this study, we provide evidence to show that the Piezo1 channel plays a similar role in hDP‐MSCs.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Recent studies have reported a role for the Piezo1 channel in regulating cell migration in endothelial cell and cancer cells . In this study, we provide evidence to show that the Piezo1 channel plays a similar role in hDP‐MSCs.…”
Section: Discussionsupporting
confidence: 66%
“…To test whether the Piezo1 channel plays a role in regulating hDP‐MSC migration, as recently reported in endothelial cell and various cancer cells, we used the wound healing assay to examine the effect of Yoda1 on cell migration (Figure ). Inclusion of 0.1‐1 μM Yoda1 in the culture medium resulted in a concentration‐dependent increase in cell migration, with 0.3 and 1 μM Yoda1 significantly accelerating cell migration at 24, 48, and 72 hours, and such stimulation was observed in hDP‐MSCs from all four donors, with some variations among the different donors (Figure A‐F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important biological feature of malignant tumors, including colon cancer, is the invasion and metastasis of tumor cells. Piezo1 is involved in gastric cancer cell migration and invasion (Yang et al 2014;Zhang et al 2018). Our findings revealed that overexpressed Piezo1 promoted colon cancer cell migration and motility.…”
Section: Discussionmentioning
confidence: 54%